Rapid voltammetric method for quinine determination in soft drinks. (1st July 2018) - Buleandra, Mihaela; Rabinca, Andreea A.; Cheregi, Mihaela C.; Ciucu, Anton A.
Highlights: Pencil graphite electrode electrochemically pretreated. Quinine (QN) determination without previous separation. The voltammetric method presented a limit of detection of 2 × 10 −7  M for QN. Surface contamination is avoided by using a disposable sensor. Abstract: A novel voltammetric assay for quinine (QN) determination using an electrochemically pretreated pencil graphite electrode is described. The detection limit of QN was 2 × 10 −7 M. The method possesses some obvious advantages including extreme simplicity, rapid response, and low cost.